The maternity of women crack users and the role of other caregivers - Camargo, Paola de Oliveira (2021)
This study aims to know the experiences of crack users with the mother figure and the participation or not of their partners in the care of their children. This is a qualitative study, using: participant observation, field diary and semi-structured interviews with five women. Data collected in the territory for four months and analyzed using Interpretivism. It was observed that in relation to the maternal figure, most of the reports are permeated by conflicts. As for the parent, most mothers do not have the same care, in some cases there is financial support. The study shows that, even permeated by conflicts, the support of parents with childrearing is of paramount importance and that regarding the relationship of crack users with the mother figure, the results are permeated by individual experiences and their family constructions. It is necessary that the health team pay attention to the service aiming at welcoming and listening.